Coupling Coordination of Water Governance and Tourism: Measurement and Prediction - Yuqing Geng; Mukasar Maimaituerxun; Han Zhang (Discrete Dynamics in Nature and Society)
The interaction between water governance and tourism is complicated and significant so that the study of the coupling coordination between these two subsystems is important. This study analyzes the correlation mechanism of the water governance-tourism system, constructs the composite and aggregated evaluation system which consists of 5 dimensions and 15 indicators, uses information entropy weight technique for order preference by similarity to an ideal solution method to evaluate the development degrees of both water governance and tourism growth of the 11 regions in the Yangtze River Economic Zone, analyzes the two subsystems’ relation of coupling coordination temporally and spatially with the coupling coordination degree model, predicts degrees of coupling coordination of the regions for the next 4 years with gray system prediction model, and proposes specific and generalizable countermeasures. The results show that these methods can provide an effective reference to evaluate the coupling coordination development of water governance and tourism and to provide scientific and generalizable countermeasures for enhancement.